PENGARUH MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE (IOC) TERHADAP KETERAMPILAN KERJA SAMA SISWA PADA MATERI KEBERAGAMAN SUKU BANGSA DI INDONESIA KELAS IV SD NEGERI 1 KELAPA - Gieska; Adi saputra; Sisi Pitriyana (Universitas Muhammadiyah Bangka Belitung, 2023)
The purpose of this research is to ascertain how the Inside Outside Circle (IOC) learning paradigm has affected the students' ability to cooperate while discussing the ethnic variety in Indonesia. With a one-group pretest-posttest pre-experimental design, this research used a quantitative approach. The Inside Outside Circle (IOC) learning technique was used in this study at SD Negeri 1 Kelapa. All of the fourth-graders at SD Negeri 1 Kelapa constituted the study's population, and the sample was chosen using the Saturated Sampling method. The class IV sample for this study has a total of 21 pupils. The data were gathered via observation. In this study's data analysis, both normality tests and hypothesis testing were used. The Inside Outside Circle (IOC) learning model has an impact on fourth-grade students' cooperation skills in the content on ethnic diversity in Indonesia at SD Negeri 1 Kelapa, according to calculations using the t-test, which revealed that the value, t-count = 12.203 > t-table = 1.725, then Ha is accepted.